Efficient femtosecond optical parametric amplification and wavelength conversion in silicon waveguides - Liu, H.; Wang, Z.; Wen, J.; Huang, N.; Sun, Q. (ALT Proceedings, 2026)
Efficient femtosecond optical parametric amplification and wavelength conversion via four-wave mixing (FWM) in silicon waveguides are demonstrated. In the femtosecond FWM process, the spectra are greatly broadened, and it is difficult to achieve efficient wavelength conversion and parametric amplification when the pump and signal pulse widths are close to or less than 100 fs because of the spectral overlap. The spectral overlap can be suppressed by tailoring the dispersion profiles of the silicon waveguides, and separable spectra are obtained for parametric amplification with 200 fs pulses. On-chip parametric gain as high as 26.8 dB and idler conversion gain of 25.6 dB is achieved with a low pump peak power over a flat bandwidth of 400 nm in a 10-mm-long dispersion engineered silicon waveguide. In addition, the impact of initial chirp on the wavelength conversion is also investigated, and relative narrower FWM spectra with most of the energy remain in the central peak can be obtained using appropriate initial chirp. The conversion bandwidth greater than 500 nm with peak conversion efficiency of -1.6 dB can be obtained.